Aquifer characteristics and groundwater potential for domestic requirements in Kediri Regency, Indonesia - Setyawan Purnama; Ahmad Cahyadi; Andung Bayu Sekaranom; Erik Febriarta; Anugrah Jorgi Firmansyah; Indra Agus Riyanto (Brawijaya University, 2023)
Like other natural resources, groundwater is also being exploited at an increasing rate, especially for domestic requirements. Groundwater is preferred as a domestic water source because of its continuous availability and relatively good quality. Unfortunately, not all places have sufficient groundwater availability of good quality. The purpose of this study was to analyze the characteristics of the aquifer in the study area and evaluate its groundwater potential for domestic needs. Aquifer characteristics were determined based on geological and geomorphological conditions, while groundwater potential was calculated using a static approach. The results showed that the characteristics of the aquifers in Kediri Regency are various. In the eastern and central parts of the study area, the characteristics of the aquifer can be in the form of unconfined aquifers with high productivity. In the western part, most of them have non-aquifer material, so it is difficult to find groundwater. Groundwater generally fills joints and diaclase formed in andesitic lava with low discharge. Although the conditions of the aquifer are various, in general, the potential for groundwater in Kediri Regency can still support its requirements because the potential for groundwater in Kediri Regency is 71,121,313,394 m3, while domestic requirements is 52,348,490 m3/year.